2018
DOI: 10.1111/aas.13216
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of analgesic efficacy between two approaches of paravertebral block for thoracotomy: A randomised trial

Abstract: We suggested that paralaminar approach provided superior analgesia for thoracotomy rather than the intercostal approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 22 publications
(23 reference statements)
1
20
1
Order By: Relevance
“…For example, the paralaminar in-plane approach provided wider sensory block and superior analgesia than the intercostal approach when 20 mL of 0.5% ropivacaine was injected at the start and end of surgery, followed by continuous infusion of 0.2% ropivacaine at 5 mL/hour 21. In one of the previous studies involving repeated bolus injection of a local anesthetic into the TPVS, a landmark-based technique was used 15.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the paralaminar in-plane approach provided wider sensory block and superior analgesia than the intercostal approach when 20 mL of 0.5% ropivacaine was injected at the start and end of surgery, followed by continuous infusion of 0.2% ropivacaine at 5 mL/hour 21. In one of the previous studies involving repeated bolus injection of a local anesthetic into the TPVS, a landmark-based technique was used 15.…”
Section: Discussionmentioning
confidence: 99%
“…According to our experience, single-injection of 20ml ropivacaine 0.375% via PL approach could acquire 4-5 dermatomes of sense blockade, which was consistent with Yasuko Take's conclusion. 7 They found the blocked dermatomes of sense loss in group PL were more than in group IC, The average of blocked dermatomes was 3 in group IC and 4 in group PL. Besides, the PL approach was regarded as a better choice to block the dorsal ramus of thoracic nerves.…”
Section: Resultsmentioning
confidence: 93%
“…The intercostal (IC) and paralaminar (PL) approaches are commonly used in TPB. Yasuko Taketa et al [7] considered that a single injection of 20ml ropivacaine 0.375% via the PL approach could acquire 4-5 dermatomes of sense blockade. They found that the blocked dermatomes of sensory loss in PL group were more than in IC group.…”
Section: Discussionmentioning
confidence: 99%